2016
DOI: 10.1007/s00586-016-4649-3
|View full text |Cite
|
Sign up to set email alerts
|

Global tilt: a single parameter incorporating spinal and pelvic sagittal parameters and least affected by patient positioning

Abstract: GT appears to be the most reliable single sagittal plane parameter in ASD. It is the least affected by patient position and incorporates both the pelvic and the spinal alignment within one measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 17 publications
5
41
0
4
Order By: Relevance
“…Among spine pelvic parameters, low incidence angle, PT, and GT are the predominant factors. This is in accordance with the suggestions of previous literature [24]. The impact of lower limbs parameters is significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among spine pelvic parameters, low incidence angle, PT, and GT are the predominant factors. This is in accordance with the suggestions of previous literature [24]. The impact of lower limbs parameters is significant.…”
Section: Discussionsupporting
confidence: 93%
“…The understanding of sagittal alignment is now considered a key point in the evaluation of spinal degeneration as well as in hip or knee pathology as imbalance correlates with disability, pain, and suboptimal evolution after surgery [23,29]. Spinal imbalance causes the implementation of compensatory mechanisms including spine and lower limbs adaptation [24]. This study points out the magnitude of the imbalance problems in a current practice data base of spinal stenosis patients and the parasitic effects of lower limbs associated pathologies.…”
Section: Resultsmentioning
confidence: 86%
“…The question raised in the Letter to the Editor concerning Global Tilt parameter [1] is very important to understand spinal balance, and we completely agree with the authors.…”
Section: Dear Editorsupporting
confidence: 64%
“…One possible explanation is the fact that while some early research showed associations between both CM and SM with health-related quality of life (HRQoL) [15], other influential studies did not find substantial correlation of CM with HRQoL [16]. In this scenario, correction of SM has received substantial attention in the literature [17], and rules for very precise calculation of the amount of correction needed in the sagittal plane are widely available [18,19].…”
Section: Discussionmentioning
confidence: 99%